Blendas de PHBV e PCL para uso em dispositivos de osteossíntese - Casarin, Suzan Aline (2010)
This study aimed to develop and characterize polymer blends using biodegradable and bioabsorbable polymers poly (hydroxybutyrate-co-valerate) PHBV with 12% valerate, and poly (ε-caprolactone) PCL, in order to make the PHBV less fragile for applications such as osteosynthesis devices. We studied the binary mixture of these polymers in the compositions PHBV / PCL (75/25 and 50/50). The polymer blends were prepared in order to simulate a large-scale industrial process, by extrusion followed by injection. The pure polymers and polymer blends were evaluated and characterized by: Melt Flow Index (MFI), Thermal Analysis (TG, DSC and DMTA), Optical Microscopy, Scanning Electron Microscopy (SEM), Thermal Test of the Heat Deflection Temperature (HDT), Mechanical Tests (impact, tensile and flexural), Size Exclusion Chromatography (SEC), analysis of in vitro degradation and Cytotoxicity Analysis, direct and indirect. The results obtained through different techniques indicated the immiscibility of PHBV / PCL blends. In terms of mechanical properties, the polymer blends analyzed indicated better characteristics than copolymer PHBV, presenting a less brittle behavior. In the in vitro study, in phosphate buffered saline solution with pH 7.3, the PHBV and PCL samples indicated a slow degradation behavior when compared to other bioabsorbable polymers. Along the degradation period, the polymers became more rigid, increasing the values of the Tensile Modulus of Elasticity. It was verified that, depending on the degradation period, there was a reduction in the values of molar masses of the samples studied. Through the cytotoxicity analysis, it was found that the pure polymers and the blends studied did not indicate indirect toxicity. However, the results indicated toxicity through the direct contact with the polymers studied, which may be related to the superficial characteristics thereof.